Os odontoideum: database analysis of 260 patients regarding etiology, associated abnormalities, and literature review - Menezes, Arnold H. (Frontiers in Surgery, 2023)
Introduction Since the first description of os odontoideum in 1886, its origin has been debated. Numerous case series and reports show both a possible congenital origin and origin from the secondary to craniovertebral junction (CVJ) trauma. We conducted a detailed analysis of 260 surgically treated cases to document the initial symptoms, age groups, radiographic findings, and associated abnormalities, aiming to enhance the confirmation of the etiology. A literature search (1970–2022) was performed to correlate our findings. Methods and materials A total of 260 patients underwent surgical management of a referral database of 520 cases (1978–2022). All patients were examined by plain radiography and myelotomography as needed until 1984, and since then, CT and MRI have been employed. History of early childhood (aged below 6 years) CVJ trauma was investigated, including obtaining emergency department's initial radiographs from the referral and subsequent follow-up. Associated radiographic and systemic abnormalities were noted, and the atlas development was followed. Results The age of the patients ranged from 4 to 68 years, mostly between 10 and 20 years. There were 176 males and 86 females. Orthotopic os odontoideum was identified in 24 patients, and 236 patients had dystopic os odontoideum. Associated abnormalities were found in 94 of 260 patients, with 73 exhibiting syndromic abnormalities and 21 having Chiari I malformation. Two sets of twins had spondyloepiphyseal dysplasia. Of 260 patients, 156 experienced early childhood trauma /. Among these, 54 initially presented with normal radiographs but later demonstrated anterior atlas hypertrophy. In addition, a smaller posterior C1 arch was observed, leading to the development of os odontoideum. Two children had initial CVJ trauma as documented by MRI, with subsequent classical findings of os odontoideum and atlas changes. Syndromic patients had an earlier presentation. The literature reviewed confirms the multifactorial etiology. Conclusions The early presentation and associated abnormalities (such as Down syndrome, Klippel–Feil syndrome, Chiari I malformation, spondyloepiphyseal dysplasia, Morquio syndrome, and others) along with case reports documenting familial, hereditary, and twin presentations strongly support a congenital origin. Likewise, surgical complications are more prevalent in syndromic patients (40%) compared to 15% in other cases, as reported in the literature. The documentation of normal odontoid in early childhood trauma cases followed by the later development of os odontoideum provides evidence supporting trauma as an etiological factor. This process also involves vascular changes in both the atlas and the formation of os odontoideum. Associated abnormalities exhibit an earlier presentation and are only seen in cases with a non-traumatic origin.